MOTIVATION OF THE MAIN CHARACTER IN SUE MONK KIDD’S SECRET LIFE OF BEES - Saidah, Nur; Sunggingwati, Dyah; Asanti, Chris (Fakultas Ilmu Budaya Universitas Mulawarman, 2019)
This research to used know form motivation and special figure character in novel Secret Life of Bees by Sue Monk Kidd’s. Research type is qualitative. This study was conducted to analyze the motivation of the main protagonist in the novel Secret Life of Bees work of Sue Monk Kidd and try to connect with the sociological approach. To obtain more data about the character in the novel, library research was also conducted by the writer. The writer collected some journals, articles, and some significant notes that could be used 5as references to investigate this research. And the characters were arranged systematically, in addition to the novel itself, additional data from literature supporters, the data of journals, articles, and data from the internet. Result of research indicates that in analyzing novel Secret Life of Bees by Sue Monk Kidd’s, that character of the special figure in novel that is Lily Owen covering character: they are love, fear of failure, hope for reward, and religious feeling. And motivation in the main character’s life. The four of them make her successful to achieve her goal. Lily is successful to get away from her cruel father and goes to Tiburon with Rosaleen to know about her mother’s death in order to learn about herself. Having analyzed some motivation of the main character in the novel Secret Life of Bees, it shows that the motivations make some results for the main character. Furthermore, the writer analyzes the result of her motivation that will be accepted by the main character. Penelitian ini digunakan untuk mengetahui bentuk motivasi dan karakter tokoh khusus dalam novel Secret Life of Bees karya Sue Monk Kidd. Jenis penelitian adalah kualitatif. Penelitian ini dilakukan untuk menganalisis motivasi protagonis utama dalam novel Secret Life of Bees karya Sue Monk Kidd dan mencoba untuk terhubung dengan pendekatan sosiologis. Untuk mendapatkan lebih banyak data tentang karakter dalam novel, penelitian perpustakaan juga dilakukan oleh penulis. Penulis mengumpulkan beberapa jurnal, artikel, dan beberapa catatan penting yang dapat digunakan sebagai referensi untuk menyelidiki penelitian ini. Dan karakter disusun secara sistematis, selain novel itu sendiri, data tambahan dari literatur pendukung, data jurnal, artikel, dan data dari internet. Hasil penelitian menunjukkan bahwa dalam menganalisis novel Secret Life of Bees karya Sue Monk Kidd, karakter tokoh utama dalam novel itu adalah karakter Lily Owencovering: mereka adalah cinta, ketakutan akan kegagalan, harapan akan hadiah, dan perasaan religius. Dan motivasi dalam kehidupan karakter utama. Keempatnya membuatnya sukses untuk mencapai tujuannya. Lily berhasil melarikan diri dari ayahnya yang kejam dan pergi ke Tiburon bersama Rosaleen untuk mengetahui tentang kematian ibunya untuk mengetahui tentang dirinya sendiri. Setelah menganalisis beberapa motivasi karakter utama dalam novel Secret Life of Bees, itu menunjukkan bahwa motivasi membuat beberapa hasil untuk karakter utama. Selanjutnya, penulis menganalisis hasil motivasinya yang akan diterima oleh tokoh utama.